Artificial Intelligence... Application in Agriculture - Kanika, Kanika; Priyanka, Priyanka; Latika, Latika; Kumar, Daksh (Indian Farming, 2019)
Artificial intelligence is different from natural intelligence displayed by humans and other living organisms. It encompasses working ecosystem of intelligent agents. In the line of cognitive scientific behavior, an ability in devices are developed using principles of computer science (programming), electronics and communication (sensors), and mechanical engineering (powering energy). These agents including devices perceive their environment and take actions that maximize their chances of successfully achieving their goals. In lay mansâ€™ language it is â€œability of a system to correctly interpret external data, to learn from these data, and use those learning to achieve specific goals and tasks through flexible adaptationâ€. It is a process of a machine mimicking the cognitive functions that are associated with brain functions such as learning and subsequently solving the problem based on that learning. AI is any technology that emulates human performance by learning, reaching conclusions, understanding complex content. AI is applicable to any intellectual task.